1999
DOI: 10.2466/pr0.1999.85.3.973
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Evaluation of Depression in Children in Egypt, Kuwait, and the United States

Abstract: The English version of the Arabic Children's Depression Inventory, constructed by Abdel-Khalek, was applied to a sample of 535 U.S. students (11 to 18 years old). Cronbach coefficients alpha were .88, .90, and .89 for boys, girls, and all subjects, respectively. Seven factors were extracted by principal axis factor analysis (Negative mood and self-depreciation, Fatigue, Lack of loneliness, Sleep problems, Weak concentration, Pessimism, and Feeling happy), denoting clear factorial structure; however, the scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…For example, Abdel-Khalek (2003) found that Kuwaiti girls reported higher scores than Kuwaiti boys on the total depression scale and on all subscales, with the exception of weak concentration. Additionally, in a cross-cultural comparison study, Abdel-Khalek and Soliman (1999) found no sex differences for depression in the American sample, but did find sex differences for the egyptian and Kuwaiti samples. egyptian girls had a higher mean score on depression than egyptian boys, while Kuwaiti boys had a higher mean score than girls.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Abdel-Khalek (2003) found that Kuwaiti girls reported higher scores than Kuwaiti boys on the total depression scale and on all subscales, with the exception of weak concentration. Additionally, in a cross-cultural comparison study, Abdel-Khalek and Soliman (1999) found no sex differences for depression in the American sample, but did find sex differences for the egyptian and Kuwaiti samples. egyptian girls had a higher mean score on depression than egyptian boys, while Kuwaiti boys had a higher mean score than girls.…”
mentioning
confidence: 88%
“…Similarly, Afifi (2006) found that egyptian girls reported more depression than egyptian boys, and Omani boys reported more depression than Omani girls. these differences could be due to many factors, including differences in the measures used or cultural differences in acknowledgement of depression, sample characteristics, and study methods-particularly age, research design, and methods of case ascertainment (Abdel-Khalek & Soliman, 1999;tepper, et al, 2008).…”
mentioning
confidence: 99%
“…The absence of information on the validity and reliability of instruments is particularly acute in Tanzania. The validation of instruments across different cultural groups is crucial to provide evidence of the scales sensibility to cultural diversity (Abdel-Khalec & Soliman, 1999). The information provided by the screening scales is critical for the decision-making process, as it enables practitioners to differentiate people with mental disorders from those without, and to identify those disorders that may need immediate intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tomás-Sábado and Gómez-Benito (in press) have developed and validated the Spanish Death Anxiety Inventory. Thus, cross-cultural comparison of personality and psychopathology, based mainly on university undergraduates, has become more common with the help of these scales (see e.g., Abdel-Khalek & Lester, 1999, Abdel-Khalek & Soliman, 1999; Lester & Abdel-Khalek, 1998).…”
mentioning
confidence: 99%